TRAINING ON PRAYER PROCEDURES FOR ELEMENTARY SCHOOL-AGED CHILDREN IN TENAM VILLAGE USING THE DEMONSTRATION METHOD - Andri Astuti; Maisarah Gusvita; Indah Safitri; Istiyana Fadillah; Nasidas Qolani; Rendi Ferdian; Siti Nurhasanah (International Journal of Multidisciplinary Reseach, 2026)
This community service activity focuses on learning the proper recitation and movements of prayer (salat). Understanding and practicing the correct procedures of salat is an important aspect of Islamic religious education. This community service activity was conducted in Tenam Village and aimed at elementary school-aged students as part of the implementation of the Islamic Religious Education course. The community service activity was carried out through three main stages: preparation, implementation, and evaluation. The preparation stage included identifying problems and analyzing the needs of the target community, determining the activity targets which covered participants, location, and time of implementation, formulating clear and measurable objectives of the community service activity, preparing training materials adjusted to the age of the participants, including the pillars and requirements of salat, recitations, and the practice of prayer movements, and determining appropriate implementation methods by emphasizing direct practice and mentoring. The second stage was the implementation stage, which began with an opening session, followed by the delivery of theoretical material and continued with demonstrations of the correct procedures of salat in accordance with Islamic guidance. The third stage was the evaluation stage, which was conducted to assess the participants’ understanding and ability to perform salat correctly through observation of practice and discussions. The results of this activity showed an improvement in the participants’ understanding and skills in performing salat according to proper guidance. Before the training was conducted, most participants had limited understanding of the requirements, pillars, and correct recitations of salat. After participating in the training, which included material delivery, demonstrations, and direct practice, participants showed positive changes. They were able to mention the requirements and pillars of salat more accurately and improve their prayer movements and recitations in accordance with Islamic guidance.